2008
DOI: 10.1016/j.epsl.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical characteristics of the Ninetyeast Ridge–Andaman island arc/trench convergent zone

Abstract: The convergence tectonics of the Ninetyeast ridge (NER), upon the Andaman island arctrench system is examined through an analysis of ETOPO2 bathymetry, satellite-derived free air gravity and seismic data. Oblique subduction and the buoyancy forces arising from subduction of the NER render the subduction processes near the Andaman arc highly complex. The bathymetric expression of the NER is visible up to Lat. 10 o N but seismic reflection data indicate that it extends up to about Lat.17 o N. The gravity ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…As the volcanism leading to the emplacement of the 85°E and Ninetyeast ridges in the BOB are older (> 80 Ma), the swells associated with the initial volcanism will have subsided. Earlier derived crustal models show the presence of thicker crust with and without underplating below these ridges (Detrick and Watts, 1979;Mukhopadhyay and Krishna, 1995;Subrahmanyam et al, 1999;Grevemeyer et al, 2001;Krishna et al, 2001b;Krishna, 2003;Subrahmanyam et al, 2008;Radhakrishna et al, 2010). The present analysis revealed that both ridges, in general, are earlier investigators for the ridge south of 2ºN revealed that this part of the ridge had evolved due to frequent ridge jumps in the vicinity of the Kerguelen hot spot during the rapid northward migration of the Wharton spreading ridge (Royer et al, 1991;Krishna et al, 1999;Sager et al, 2010;Krishna et al, 2012).…”
Section: Geodynamic Implicationssupporting
confidence: 65%
See 2 more Smart Citations
“…As the volcanism leading to the emplacement of the 85°E and Ninetyeast ridges in the BOB are older (> 80 Ma), the swells associated with the initial volcanism will have subsided. Earlier derived crustal models show the presence of thicker crust with and without underplating below these ridges (Detrick and Watts, 1979;Mukhopadhyay and Krishna, 1995;Subrahmanyam et al, 1999;Grevemeyer et al, 2001;Krishna et al, 2001b;Krishna, 2003;Subrahmanyam et al, 2008;Radhakrishna et al, 2010). The present analysis revealed that both ridges, in general, are earlier investigators for the ridge south of 2ºN revealed that this part of the ridge had evolved due to frequent ridge jumps in the vicinity of the Kerguelen hot spot during the rapid northward migration of the Wharton spreading ridge (Royer et al, 1991;Krishna et al, 1999;Sager et al, 2010;Krishna et al, 2012).…”
Section: Geodynamic Implicationssupporting
confidence: 65%
“…Additionally, for the purpose of 2-D flexural analysis over the aseismic ridges, we used several short E-W seismic reflection profiles across the 85°E Ridge (Bastia et al, 2010;Radhakrishna et al, 2012;Krishna et al, 2014;Rao and Radhakrishna, 2014) and across the Ninetyeast Ridge (Curray et al, 1982;Gopala Rao et al, 1997;Subrahmanyam et al, 2008;Maurin and Rangin, 2009 …”
Section: Datasets Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…The crust beneath the 85E is between 18 and 22 km thick (~20 km thick), that is, it is thicker by~15 km than adjacent normal oceanic crust, which is 5 km thick (Subrahmanyam et al, 2001). This suggestion was followed by other authors, who proposed the presence of a thicker crust below the 90E (Detrick & Watts, 1979;Grevemeyer et al, 2001;Krishna et al, 2001;Mukhopadhyay & Krishna, 1995;Subrahmanyam, Gireesh, Chand, Kamesh Raju, & Gopala Rao, 2008). As the anomalies associated with the 90E are small, Bowin (1973) suggested also the existence of some way of compensation at depth (as the 85E compensation).…”
Section: Geological Settingmentioning
confidence: 95%
“…Based on the known volcanoes in the region, there is a distinct gap in active volcanoes from 06°N to 12°N. Subduction of the base of the Ninety-east ridge was suggested as one of the possible reasons for this gap in volcanic activity (Subrahmanyam et al, 2008). It is interesting to note the occurrence of several earthquake swarms (S1-S7, Fig.…”
Section: Geodynamic Settingmentioning
confidence: 98%